Examination of the Epiphyseal Union in Age Assessment - Yarımoğlu, Berna H; Alper, Benhan; Meral, Demet; Çekin, Necmi (The Bulletin of Legal Medicine, 2005)
Age assessment has an important place in Forensic Medicine. Estimation of the accurate age is required in some legal processes as demographic records are not properly performed in Turkey. Age determination by researching the epiphyseal union of some specific joints in the specific age groups is the commonly used method. Most commonly used methods are Greulich-Pyle and Tanner-Whitehouse methods for this purpose Greulich- Pyle method is preferred in our country usually because of easy applicability. According to some recent studies, the rate of growth and development is quicker and so the maturation occurs earlier. In our study, 570 x-rays of different ages are evaluated to test the correlation of recent methods. We found that the epiphyseal union started at the age of 16, in hand-wrist, shoulder and pelvis. At the age of 17, the epiphyseal union was completed in 100% of the hand-wrist x-ray and 81.8% of the shoulder and pelvis roentgenograms. As a result, bone age is advanced in comparison with the chronological age by using recent methods. Standard data for domestic population must be collected by means of the x-rays of healthy people having regular demographic records and new standards should be established to prevent misinterpretation of the cases. Key words: Age determination, epiphysis, hand-wrist, pelvis, shoulder.